Extra cardiac birth defects in children with congenital heart anomalies - Jan, Muzafar; Sohil, Parvaiz Rafieq; Khan, Younus Ramzan; Bashir, Amber (International Journal of Contemporary Pediatrics, 2023)
Background: Congenital heart disease (CHD) may be present with a syndrome containing known anomalies with specific physical findings or can be present with manifestations of a systemic defect that affects the heart and other systems. Aim of the study was to determine the prevalence and spectrum of extra-cardiac defects associated with CHD. Methods: This prospective and observational study was conducted in the age group of 1 day to 12 years with CHD chosen by purposive sampling technique. Informed consent was obtained from parents or guardians. The CHD was diagnosed on the basis of detailed clinical examination, chest X-ray and Electrocardiography and confirmed by 2D echocardiography. The extra-cardiac defects were diagnosed based on standard definitions and various investigations like CBC, LFT, KFT, USG abdomen and skull, CT, MRI, G-Band karyotype, fluorescence in situ hybridization (FISH) studies for micro-deletions, audiometry, ophthalmologic evaluation and thyroid hormone profile. Results: A total of 61,254 patients were examined during the study and 640 children were identified with CHD. So, the prevalence was 10.14 per 1000 live births. Out 640 children enrolled in the study 352 (55%) were males and 288 (45%) were females with a male female ratio of 1.2:1 and 520 (81.3%) had acyanotic CHD (ACHD) and 120 (18.3%) had cyanotic CHD (CCHD). The majority of the children with CHD belonged to the second birth order 360 (56.2%). The extra-cardiac anomalies were present in 128 (20%) cases. Out of them 77 (12%) cases had extra-cardiac anomalies associated with acyanotic CHD and 51 (8%) cases had extracardiac anomalies associated with cyanotic CHD. Out of 128 cases with extra-cardiac defects 64 (50%) cases were syndromic, 51 (39.8) cases had multiple congenital defects and 13 (10.2%) had laterality defects. Conclusions: The CHD is often associated with various extra-cardiac abnormalities.